Fixation of unstable femoral juvenile osteochondritis dissecans lesions with bioabsorbable pins: clinical and radiographic outcomes - Kreher, Jannes; Nolte, Anna-Katharina; Wünnemann, Felix; Berrsche, Gregor; Rehnitz, Christoph; Barié, Alexander; Schmitt, Holger (Journal of Clinical Medicine, 2023)
Juvenile Osteochondritis Dissecans (JOCD) is a common reason for knee pain among children. The aim of this case study was to report on clinical and radiographic outcomes after fixation of an osteochondral fragment with bioabsorbable pins in children with open growth plates. We hypothesized that surgical treatment with this technique will result in good function, high rates of radiographic healing and high return to sport rates. A total of 13 knees in 12 patients (6 male, 6 female) with a median of 13 years (11, 17) were evaluated retrospectively at a minimum clinical follow-up of 24 months. Inclusion criteria were defined as open growth plates and an unstable osteochondral lesion grade III or IV. The clinical outcome was evaluated utilizing three standardized patient-reported outcome scores (Tegner Activity Scale [TAS], Knee Injury and Osteoarthritis Outcome Score [KOOS], Lysholm Score). All patients underwent magnetic resonance imaging 15 months (3, 34) after surgical treatment and defect healing was evaluated utilizing a modified version of the Magnetic Resonance Observation of Cartilage Repair Tissue (MOCART) score. Due to the small sample size, the data was reported descriptively. The interobserver variability was calculated with the Spearman rank correlation coefficient. Comparisons were made with Wilcoxon sign rank test (or sign test). At final follow-up the median KOOS Score was 98% (79.2%, 100%) and the median Lysholm Score was 94 (69, 100) points. The Tegner Activity Scale was 7 (4, 10) points preoperatively and 7 (4,10) points postoperatively (p = 0.5). Complete bony ingrowth occurred in 9 knees (69%), complete cartilage defect repair in 10 knees (77%) and integration to the border zone was found in 11 knees (85%) 15 (3, 34) months following surgical treatment. Fixation of osteochondral fragments with bioabsorbable pins resulted in good functional and radiographic outcomes, a high return to sport- and a low complication rate among children with open growth plates.